2015
DOI: 10.1159/000375144
|View full text |Cite
|
Sign up to set email alerts
|

Food Fortification for Addressing Iron Deficiency in Filipino Children: Benefits and Cost-Effectiveness

Abstract: Iron deficiency is one of the most widespread nutritional disorders in both developing and industrialized countries, making it a global public health concern. Anemia, mainly due to iron deficiency, affects one third of the world's population and is concentrated in women and children below 5 years of age. Iron deficiency anemia has a profound impact on human health and productivity, and the effects of iron deficiency are especially pronounced in the first 1,000 days of life. This critical window of time sets th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Nutritional deficiencies are major concern in pediatric practice. Though it is a global trend, prevalence is more among developing and underdeveloped South Asian countries [4,27,29] though showing some declining trend due to enforcement of anemia surveillance programs and supplementation [30]. Deficiency of micronutrients including that of iron and its relationship to cognitive and physical functions in childhood in Indian children has been reviewed by Swaminathan S et al [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional deficiencies are major concern in pediatric practice. Though it is a global trend, prevalence is more among developing and underdeveloped South Asian countries [4,27,29] though showing some declining trend due to enforcement of anemia surveillance programs and supplementation [30]. Deficiency of micronutrients including that of iron and its relationship to cognitive and physical functions in childhood in Indian children has been reviewed by Swaminathan S et al [31].…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency anemia in childhood a common, yet a clinically important reversible state of malnutrition, has well established relationship with impaired work capacity, lowered cognitive functions, impaired immune responses and growth retardation [1][2]. Cognitive functions (memory, intelligence, and sensory perception) have been related to intelligence and its afflictions can affect academic performance and thus have a greater impact on the psyche, interpersonal relationship and social life of a child [3][4][5]. If untreated, these changes may become irreversible which makes early recognition and treatment crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Food Policy and Research Institute reported that the progress of its eradication in women in reproductive age and children under 5 years old is currently off‐course (IFPRI, ). This contrasts the pronounced economic development of the Asia Pacific region in the last decade and indicates the socioeconomic polarization of resources, which have not yet spread to rural low‐income areas where micronutrient deficiencies are more common (Detzel & Wieser, ).…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient and protein deficiencies are a global public health concern (Detzel and Wieser, 2015;NBS, 2016). Globally, pregnant women and their children below five years are at the highest risk of micronutrient deficiencies (Bailey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…IDA affects over two billion people worldwide and 190 million preschool-age children (Bailey et al, 2015;Detzel and Wieser, 2015). Iron deficiency affects 60% of children below five years In Tanzania and 58% of (NBS, 2016).…”
Section: Introductionmentioning
confidence: 99%